Distribution of Alexandrium pacificum cysts in the area adjacent to the Changjiang River estuary, China. (July 2020) - Dai, Li; Geng, Hui-Xia; Yu, Ren-Cheng; Liu, Yang; Zhao, Jia-Yu; Wang, Jin-Xiu; Zhang, Qing-Chun; Kong, Fan-Zhou; Zhou, Ming-Jiang
Abstract: The coastal waters adjacent to the Changjiang River estuary (CRE) are characterized by nutrient pollution and recurrent harmful algal blooms. In this study, resting cysts of Alexandrium pacificum Litaker and A. catenella (Whedon & Kof.) Balech, two major species within the A. tamarense species complex in Chinese coastal waters, were studied using sediment samples collected from the area adjacent to the CRE in May 2014 and December 2015. Cysts were detected with two real-time quantitative PCR assays, as well as the primuline-staining method. Only cysts of A. pacificum were found in the study area, which mainly distributed in the mud depositional zone near the CRE. A low-abundance region of the cysts present in spring is in accordance with the intrusive pathway of the Nearshore Kuroshio Branch Current (NKBC), suggesting that A. pacificum blooms could be regulated by seasonal intrusion of NKBC. Highlights: Alexandrium pacificum cysts in the East China Sea (ECS) were studied by qPCR assay. A. pacificum cysts were mainly found in the mud zone near Changjiang River estuary. Cyst distribution is affected by a Kuroshio Branch Current, NKBC, in spring. Dynamics of A. pacificum bloom will be regulated by inter-annual variation of NKBC.